Students' Challenges in Joining Virtual Exchange Program - Patria Handung Jaya; Rizka Saputri (Journal of Islamic Studies and Education, 2023)
Financial concerns, social-economic problems, time constraints, and added by the Covid-19 pandemic are some of the reasons why students can not join a student exchange program. One of the alternatives to those obstacles is a Virtual Exchange (VE) Program, where students conduct the program online from their home country. This study aims to find out what are the challenges that students have to face during their VE, and how they are dealing with those dares. This study uses qualitative methods by semi-structured interviews to add the research references of this study. In addition, the interview was conducted with four correspondents from two different VE programs. The findings confirm that students do find some challenges during their VE program. The challenges that occur from the students themselves, the classes, or even from their home university. The results also found that students need to do, and find a certain way to deal with those challenges. Based on this phenomenon, it is better for students to prepare and consider themselves before joining a VE program.